LITERARY REBELLION IN TRANSITION: THE CULTURAL LEGACY OF THE ANGRY YOUNG MEN MOVEMENT IN POST-WAR BRITAIN - Chinakov Abdulahad Muminjon ugli, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This extended paper explores the rise, development, and legacy of the "Angry Young Men" literary movement, which emerged in post-World War II Britain as a response to widespread social dissatisfaction and institutional stagnation. Characterized by class-conscious realism, anti-establishment rhetoric, and stylistic innovation, the movement provided a voice for a generation of disaffected writers and intellectuals. Through in-depth analysis of literary texts by John Osborne, Kingsley Amis, and Alan Sillitoe, this paper investigates how literature became a medium for rebellion and cultural transformation. It further considers the lasting impact of the movement on modern British literature and the relevance of its themes in the context of 21st-century socio-political challenges.